1998
DOI: 10.1128/mcb.18.5.2779
|View full text |Cite
|
Sign up to set email alerts
|

Destabilization of Yeast Micro- and Minisatellite DNA Sequences by Mutations Affecting a Nuclease Involved in Okazaki Fragment Processing (rad27) and DNA Polymerase δ (pol3-t)

Abstract: We examined the effects of mutations in the Saccharomyces cerevisiae RAD27 (encoding a nuclease involved in the processing of Okazaki fragments) and POL3 (encoding DNA polymerase ␦) genes on the stability of a minisatellite sequence (20-bp repeats) and microsatellites (1-to 8-bp repeat units). Both the rad27 and pol3-t mutations destabilized both classes of repeats, although the types of tract alterations observed in the two mutant strains were different. The tract alterations observed in rad27 strains were pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

17
168
2

Year Published

1999
1999
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(187 citation statements)
references
References 60 publications
(101 reference statements)
17
168
2
Order By: Relevance
“…During DNA replication, the hairpin formation on the template strand or on the newly synthesized strand would produce a deletion or an expansion of the repeat tract, respectively. This hypothesis is consistent with the observation that CAG-repeat instability depends on the direction in which the replication fork proceeds through the repeat tract (8,9,13,20).The repeat tract instability is also higher in the rad27-deletion mutant, which fails to process Okazaki fragments (12,14,21,22). A failure to process the Okazaki fragments may facilitate hairpin formation on the newly synthesized strand.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…During DNA replication, the hairpin formation on the template strand or on the newly synthesized strand would produce a deletion or an expansion of the repeat tract, respectively. This hypothesis is consistent with the observation that CAG-repeat instability depends on the direction in which the replication fork proceeds through the repeat tract (8,9,13,20).The repeat tract instability is also higher in the rad27-deletion mutant, which fails to process Okazaki fragments (12,14,21,22). A failure to process the Okazaki fragments may facilitate hairpin formation on the newly synthesized strand.…”
supporting
confidence: 90%
“…Several studies using model organisms indicate that replication slippage plays a major role in the repeat tract instability (7)(8)(9)(10)(11)(12)(13)(14). The latter model is also supported by the in vitro observations that CAG repeats can form hairpin structures, with the CTG hairpin being more stable than the CAG hairpin (15)(16)(17)(18).…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…This suggests that secondary structures can form in vivo and impair replication/repair enzymes. Studies in model organisms, such as S. cerevisiae, have shown that mutations in DNA replication enzymes, particularly Rad27 (yeast FEN-1 homolog), lead to TNR instability (6,(22)(23)(24)(25)(26)(27)(28). Rad27/FEN-1 is a multifunctional nuclease that plays a critical role in maintaining genome stability through RNA primer removal and long patch base excision repair.…”
mentioning
confidence: 99%
“…In assays that measure chromosome instability, rad27 deletion strains are associated with di-and trinucleotide repeat instability (Johnson et al 1995), and a strong mutator phenotype (Tishkoff et al 1997;Johnson et al 1995;Kokoska et al 1998). The mutator phenotype is characterized by a 50-fold increase in the CAN1 gene mutation rate, with a bias toward duplication mutations.…”
mentioning
confidence: 99%